Effects of Levetıracetam Treatment on the Autonomic Nervous System Functions in Epilepsy Patients - Dilek YILMAZ; Burhanettin ÇİĞDEM (Archives of Epilepsy, 2020)

(untitled)
Objectives:Sudden unexpected death in epilepsy patients is considered to be the most significant epilepsy-related cause of death, and this is associated especially with uncontrolled generalized tonic-clonic seizures, cardiac arrhythmia, decreased heart rate variability, and the use of anti-epileptic drugs. In this study, we aimed to investigate the effects of levetiracetam on the autonomic nervous system by evaluating heart rate variability (HRV) in epilepsy patients using levetiracetam.Methods:The patients, in whom levetiracetam was started in monotherapy and polytherapy, were divided into two groups in this study. The first group consisted of 29 patients with newly diagnosed epilepsy, in whom levetiracetam was started, and the second group consisted of 11 patients in whom levetiracetam was added to antiepileptic drug treatment. In patients receiving monotherapy and polytherapy, the HRV values measured before levetiracetam was started and the HRV values measured three months after starting levetiracetam in the same patient groups were compared. HRV was measured by a BVP (blood volume pulse) sensor attached to the finger by performing 10-min recordings using the Nexus/BioTrace+ brand device and with frequency-domain spectral analysis.Results:According to the measurements made before starting the treatment and in the third month of the treatment, no significant difference was obtained between the Total Power (TP), Low-Frequency power (LF), High-Frequency power (HF), Very Low-Frequency power (VLF), and LF/ HF values of 29 patients taking levetiracetam in monotherapy and 11 patients taking levetiracetam in polytherapy.Conclusion:This study demonstrated that the use of levetiracetam in monotherapy and polytherapy had no significant effect on the autonomic nervous system functions.